The Effect of Mandatory IFRS Adoption on Conditional Conservatism in Europe. (16th February 2015) - André, Paul; Filip, Andrei; Paugam, Luc
Abstract We study the effect of mandatory adoption of International Financial Reporting Standards (IFRS) in Europe in 2005 on conditional conservatism. We capture conditional conservatism with a modified version of the Khan and Watts measure (C_Score) that also controls for potential shifts in unconditional conservatism and cost of capital. From a sample of 13, 711 firm‐year observations drawn from 16 European countries spanning the 2000–2010 period, we document an overall decline in the degree of conditional conservatism after the adoption of IFRS. We show that the decline in conditional conservatism is less pronounced for countries with high quality audit environments and strong enforcement of compliance with accounting standards using the Brown et al. audit and enforcement index. As asset impairment tests are a key mechanism ensuring conditional conservatism in the IFRS framework, we further examine these. We show that firms booking an asset impairment present a smaller decline in the degree of conditional conservatism relative to firms that do not. We also demonstrate that firms that do not book an asset impairment when evidence suggests the probable need to do so experience a more pronounced reduction in conditional conservatism. We argue that IFRS are conceptually conditionally conservative but that inappropriate application of conditional conservatism principles is likely to prevent financial reporting from reaching the level of conservatism targeted by the International Accounting Standards Board (IASB).